From Common Task to Doctrinal Dialogue. Theological Themes of The 11th The World Council of Churches Assembly - Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
The WCC assembly held in Karlsruhe in September 2022 started from some urgent topics—such as war and the climate crisis—but also addressed a series of underlying theological themes, such as moral discernment and the ecclesiological model. The conversations and texts emanating there constitute a good x-ray of the current ecumenical situation, in which consensus on theological issues constitutes a guarantee for communion in faith. In them the survival of the two founding souls of the WCC, Work and Life and Faith and Order, is detected. So, after the appropriate debates and discussions, also on social and environmental issues, the conclusion has been reached on the need for a theological dialogue around the debated topics of creation, peace and ethics, as well as ecclesiology and biblical hermeneutics.